PENGARUH UKURAN PERUSAHAAN DAN BOARD GENDER DIVERSITY TERHADAP ESG SCORE - Ferli Erwansyah; Ferra Maryana (Sekolah Tinggi Ilmu Ekonomi Nasional (STIENAS) Banjarmasin, 2025)
Abstract, This study aims to examine the effect of firm size and board gender diversity on the ESG scores of companies listed on the IDX Sustainability Index (IDX) that have been assigned ESG scores by Morningstar Sustainalytics, in collaboration with IDX, for 2024. The research method used was quantitative with cross-sectional data. The population was 80 companies listed on the IDX Sustainability Index that had been assigned ESG scores by Morningstar Sustainalytics, with a sample size of 48 companies. The results showed that board gender diversity significantly impacted ESG scores, while firm size did not.